(4-x^2) 8+x^3 (5+y)^3 используя формулы сокращенного умножения

(4-x^2) 8+x^3 (5+y)^3 используя формулы сокращенного умножения
Гость
Ответ(ы) на вопрос:
Гость
(4-x^2) = (2-x)* (2+x) 8+x^3 = (2 + x)*(4+2x+x^2) (5+y)^3 = 125 + 75y + 15*y^2+y^3
Гость
4-x² = (2-x)(2+x) 8+x³ = (2+x)(4-2x+x²) (5+y)³ = 25+3*25*y+3*5*y²+y² = 25+75y+15y²+y² = 25+75y+16y² ФОРМУЛЫ СОКРАЩЕННОГО УМНОЖЕНИЯ: (a+b)² = a²+2ab+b² (a-b)² = a²-2ab+b² a²-b² = (a-b)*(a+b) (a+b)³ = a³+3a²b+3ab²+b² (a-b)³ = a³-3a²b+3ab²-b² a³+b³ = (a+b)*(a²-ab+b²) a³-b³ = (a-b)*(a²+ab+b²)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы